2016
DOI: 10.1111/hiv.12390
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of mitochondrial DNA mutations in HIV‐infected treatment‐experienced individuals

Abstract: ObjectivesWe recently observed a decrease in deoxyribonucleotide (dNTP) pools in HIV‐infected individuals on antiretroviral therapy (ART). Alterations in dNTPs result in mutations in mitochondrial DNA (mtDNA) in cell culture and animal models. Therefore, we investigated whether ART is associated with mitochondrial genome sequence variation in peripheral blood mononuclear cells (PBMCs) of HIV‐infected treatment‐experienced individuals.MethodsIn this substudy of a case−control study, 71 participants were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Furthermore, we validated our results using data from an independent cohort enrolled at Yale New Haven Hospital, New Haven, Connecticut, USA (Li et al, ) (Li et al, ). We included in the current analysis data from study participants living with HIV who were either current smokers or never smokers.…”
Section: Methodsmentioning
confidence: 56%
See 3 more Smart Citations
“…Furthermore, we validated our results using data from an independent cohort enrolled at Yale New Haven Hospital, New Haven, Connecticut, USA (Li et al, ) (Li et al, ). We included in the current analysis data from study participants living with HIV who were either current smokers or never smokers.…”
Section: Methodsmentioning
confidence: 56%
“…The second study demonstrated increased mtDNA deletions in muscle tissue from participants treated with HIV therapy ( n = 21) compared to those who were therapy‐naïve ( n = 11), but showed no evidence of increased mtDNA heteroplasmy (Payne et al, ). Finally Li et al () reported a significantly higher frequency of mtDNA variants among persons living with HIV and treated with cART ( n = 47) compared to HIV‐negative controls ( n = 24).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In fact, mitochondrial defections have been associated with increased rates of preterm delivery, stillbirth, IUGR, and sudden infant death [5][6][7][8]. Reviewing the literature, ART can induce subclinical transplacental mitochondrial lesions.…”
mentioning
confidence: 99%